PENGARUH LOAN TO DEPOSIT RATIO DAN NON PERFORMING LOAN TERHADAP NILAI PERUSAHAAN DENGAN RETURN ON ASSETS SEBAGAI VARIABEL INTERVENING PADA BANK UMUM YANG TERDAFTAR DI BEI TAHUN 2019-2021 - Riskiya, Siti; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this study is to investigate the influence of Loan to Deposit Ratio and Non Performing Loans on Firm value with Return On Assets as an intervening variable in commercial banks listed on the Indonesia Stock Exchange for the years 2019-2021. The population in this study comprises all commercial banks listed on the Indonesia Stock Exchange during 2019-2021, totaling 47 banks. the sampling technique used in this research is purposive sampling, resulting in 11 samples for data analysis. Data analysis and hypothesis testing are conducted using the Smart PLS 3.0 application. the results of this study indicate that Loan to Deposit Ratio and Non-Performing Loans have a positive but not significant impact on Return On Assets. The Loan to Deposit Ratio has a significant negative impact on Firm value, while Non-Performing Loans and Return On Assets have a significant positive impact on Firm value. Loan to Deposit Ratio and Non Performing Loans have a positive but not significant influence on Firm value through Return On Assets.